El control político como requisito del Estado constitucional. Evolución histórica - Enríquez Fuentes, Gastón J. (2023)
The concept of constitution sends to the study about the political control. The question of the government political control is, actually, the base of any government system. This article searches for the topic since the ancient times to the Entitlement State, passing across the middle age, the modern age and the contemporary age.